Kepastian Hukum Peradilan Hak Berdasarkan Akta Perikatan Jual Beli dan Akta Kuasa Jual yang Dibuat Berkaitan atas Perjanjian Hutang Piutang yang Dibuat secara Notariil (Studi Putusan Mahkamah Agung Nomor: 118/K/Pdt/2022) - Lubis, Muhammad Iqbal (Medan Resource Center, 2023)
This normative juridical legal research study aims to describe the legal strength and consequences of sale and purchase agreements and power of attorney related to debt and credit agreements, as well as the legal certainty of their transfer based on a notarized agreement. Data sources include primary and secondary data. Results indicate that sale and purchase agreements and power of attorney made before a notary without lawful cause do not have legal force, and cannot be used as a basis for bonds guarantee of debt and receivables. Transfer of rights based on sale and purchase agreements and power of attorney related to debt and credit agreements also do not have legal force, and can be considered null and void if there is evidence of bad faith. The Supreme Court decision No. 118 K/Pdt/2022 upheld the validity of the sale and purchase agreement and power of attorney in a case where the parties were not under coercion or deception when carrying out the agreement.